On the Importance of the Starting Material Choice and Analytical Procedures Adopted When Developing a Strategy for the Nanoencapsulation of Saffron (Crocus sativus L.) Bioactive Antioxidants - Maria Z. Tsimidou (MDPI AG, 2023)
Saffron is known as the most expensive spice in the world. It is comprised of the dried stigmas of the pistil of the Crocus sativus L., which is a cultivated, sterile crocus plant. This plant material is now recognized as the unique edible source of certain bioactive apocarotenoids for which in-vivo antioxidant properties have been reported. Among the latter, crocins, red-orange natural colorants, and their parent molecule crocetin prevail in bioactivity significance. This review is focused on the strategies developed so far for their nanoencapsulation in relation to the characteristics of the starting material, extraction procedures of the bioactive antioxidants and analytical methods applied for their characterization and quantification throughout the process. The literature so far points out gaps that lead to publishable data, on one hand, but not necessarily to repeatable and meaningful processes due to incomplete characterization of the starting and the released material in efficiency and stability studies of the nanoencapsulates. Accurate terminology and quantitative chromatographic or spectrophotometric procedures for the determination of the core compounds are needed. Authenticity control and quality of saffron samples, and the verification of the concentrations of compounds in commercial preparations labeled as 'crocin,' are prerequisites in any experimental design setup.